Composición química y capacidad antioxidante del fruto de Hesperomeles obtusifolia “sachón” procedente de los páramos de Piura - Uribe Villarreal, José Carlo (2020)
The fruit of the "sachon" contains minerals and phenolic compounds that give it an important nutraceutical potential. The objective was to evaluate the chemical composition and antioxidant capacity of the fruit of Hesperomeles obtusifolia "sachon" from the páramos of Piura. The lipids, proteins and carbohydrates were determined by the Soxhlet, Kjeldahl and Fehling methods, respectively. The minerals (calcium, iron, sodium and magnesium) were determined by atomic absorption spectroscopy. Three extracts (aqueous, ethanol, and decoct) were prepared. The total phenolic compounds, total flavonoids, and total anthocyanins by Folin-Ciocalteu, AlCl3 and differential pH were determined, respectively. The antioxidant capacity was analyzed by DPPH, FRAP and ABTS were determined. The lipids, proteins and carbohydrates were 0.75, 8.26 and 1.49 g/100 g lyophilized fruit (LF) respectively. The concentrations of Ca, Mg, Na and Fe were 267.83; 66.75; 9.37 and 6.09 mg/100 g LF respectively. The total phenolic compounds fluctuated between 13.89±0.52 and 7.30±1.47 mg GAE/g LF, the total anthocyanins found were between 0.53±0.01 and 2.06±0.02 mg C3GE/g LF, total flavonoids between of 4.33±0.03 and 5.84±0.04 mg QE/g LF. The antioxidant capacity values fluctuated between 4.12±0.12 - 6.40±0.62 mg ET/g LF (DPPH), 0.40±0.01 - 0.63±0.02 mg ET/g LF (FRAP) and 4.79±0.17 - 8.37±0.97 mg ET/g LF (ABTS). It is concluded that the chemical compounds confer antioxidant capacity to the fruit of Hesperomeles obtusifolia, making it an important source of nutritional value